Avaliação e monitoramento de políticas públicas: criação de um modelo sistêmico aplicado ao Instituto de Assistência Técnica e Extensão Rural do Rio Grande do Norte (EMATER-RN) - Paulino, Hideljundes Macedo (2014)
The nature of this thesis is interventionist and aims to create an alternative on how to control and evaluate the public policies implementation developed at the Institute for Technical Assistance and Rural Extension of Rio Grande do Norte State. The cenarium takes place in a public institution , classified as a municipality that belongs to the Rio Grande do Norte government and adopts the design science research methodology , where it generates a set of artifacts that guide the development of a computerized information system . To ensure the decisions, the literature was reviewed aiming to bring and highlight concepts that will be used as base to build the intervention. The use of an effective methodology called Iconix systems analysis , provides a software development process in a short time . As a result of many artifacts created by the methodology there is a software computer able of running on the Internet environment with G2C behavior, it is suggested as a management tool for monitoring artifacts generated by the various methods. Moreover, it reveals barriers faced in the public companies environment such as lack of infrastructure , the strength of the workforce and the executives behavior